Effects of Lumajang sand-bentonite mix on Al-Si casting mechanical properties - Edi Widodo; Rendra Dani Firmansyah; Subroto; Iis Siti Aisyah (University of Muhammadiyah Malang, 2023)
The use of sand for metal molds is often found in various places; this research will focus on the type of sand used, namely sand from Lumajang Regency, which is known to be strong for concrete mixes or the like. So the purpose of this research is to find out how Lumajang sand molds will be used as metal casting molds. Testing will be carried out by making three variations of bentonite mixtures: 10%, 15%, and 20%. Later, after knowing the tensile and compressive strengths of each sand mold, casting will be carried out with three variations. For testing, casting objects will use the dye penetration test method. So that a description of the surface smoothness of the casting objects made from the three molds will be obtained and it will be known which variation is good to know about the sand mold and the appropriate metal casting results. From the results of the research conducted, it shows that the bentonite mixture with a percentage of 20% gets the highest compressive value with a value of 26.3 N/cm2 when compared to other bentonite mixture variations. From the tensile testing results, a high tensile strength value was obtained in the 15% bentonite mixture variation with a value of 0.7 N/cm2. While the results of the dye penetrant test were obtained, the results of the variation of the sand mold mixture with 20% bentonite into a mold produced the smoothest workpiece results with a few red spots caused during testing.